2020
DOI: 10.13057/biodiv/d220115
|View full text |Cite
|
Sign up to set email alerts
|

The structure and composition of macrozoobenthos community in varying water qualities in Kalibaru Waters, Bengkulu, Indonesia

Abstract: Abstract. Lilisti, Zamdial, Hartono D, Brata B, Simarmata M. 2021. The structure and composition of macrozoobenthos community in varying water qualities in Kalibaru Waters, Bengkulu, Indonesia. Biodiversitas 22: 106-112. Various human activities affect the quality of the aquatic ecosystem that can be assessed by measuring the physical, chemical, and biological parameters of the waters and sediments. This is the case of Kalibaru Waters, Bengkulu, Indonesia which shows changes in the estuary and marine ecosystem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This study has several data limitations that require deeper investigation, including the substrate condition in each station i.e clay, sand, and silt [1]. Other studies also reported that the occurrence of benthic macrofauna was related to water velocity for species dwelling on the surface or with low mobility [12]. Therefore, further research on other taxa groups, such as plankton and fishes, is needed to increase the understanding of the habitat condition related to the anthropogenic effect on stream conditions in the Purba District.…”
Section: Resultsmentioning
confidence: 85%
“…This study has several data limitations that require deeper investigation, including the substrate condition in each station i.e clay, sand, and silt [1]. Other studies also reported that the occurrence of benthic macrofauna was related to water velocity for species dwelling on the surface or with low mobility [12]. Therefore, further research on other taxa groups, such as plankton and fishes, is needed to increase the understanding of the habitat condition related to the anthropogenic effect on stream conditions in the Purba District.…”
Section: Resultsmentioning
confidence: 85%
“…The taxa recorded during the research are 62, 9, and 7 genus for marine, estuary, and downstream sites, correspondingly; Gastropods are the most dominant class. This number is relatively high compared to Lilisti et al (2021) and Rimadiyani (2019) research results. Nevertheless, the number is smaller than previous studies outside Indonesia waters.…”
Section: Composition Abundance and Distribution Of Macrozoobenthosmentioning
confidence: 71%
“…Echinoderms and Gastropods are the two major classes that make up the macrozoobenthos community in the coastal waters of Marsegu Island (Yunita et al 2018). In contrast, in Kalibaru Waters of Bengkulu, the dominant macrozoobenthos class is Pelecypoda (Lilisti et al 2021).…”
Section: Composition Abundance and Distribution Of Macrozoobenthosmentioning
confidence: 87%